THE ROLE OF NISIN, POTASSIUM SORBATE AND SODIUM LACTATE AS ADDITIVE IN IMPROVING THE CHEMICAL AND QUALITATIVE CHARACTERISTICS OF CHILLED GROUND BEEF. - Narjis S. A. Mula; Alrubeii A. M. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was conducted to evaluate the effects of nisin, potassium sorbate and sodium lactate and their interactions as preservatives in fat oxidation, some quality and microbial characteristics of chilled ground beef meat stored at 4C˚ for 0,4,8 and 12 days. The study included nine different treatments: T1 (control treatment without addition), T2 (nisin at a concentration of 150 mg/kg), T3 (potassium sorbate 0.075 g/kg), T4 (sodium lactate 3%), T5 (nisin 150 mg/kg + potassium sorbate 0.075 g/kg), T6 (nisin 150 mg/kg + sodium lactate 3%), T7 (Sodium Lactate 3% + Potassium Sorbate 0.075 g/kg), T8 (Nisin 150 mg/kg + Sodium Lactate 3% + Potassium Sorbate 0.075 g/kg) and T9 (Addition of Butylated hydroxyanisole(BHA 0.01%)). All treatments showed significant (p<0.01) decreases in dry matter percentage of (fat and ash) and increase in protein and moisture and water holding capacity (WHC) percentage as compared with the control treatment at any refrigerated storage time. Thiobarbituric acid (TBA) were lower (P<0.01) in nisin, potassium sorbate and sodium lactate treatments when compared with the control treatment at any refrigerated storage time. Nisin, potassium sorbate and sodium lactate treated samples reduced (P<0.01) the total plate count of bacteria during refrigerated storage times. It can be concluded that nisin, potassium sorbate and sodium lactate had positive significant influence on quality characteristics and microbial safety of ground beef meat when stored under refrigeration at 4C° up to 12 days.